2001
DOI: 10.1006/lich.2001.0353
|View full text |Cite
|
Sign up to set email alerts
|

Accurate lifespan estimates cannot be obtained from 14C profiles in the crustose lichen Rhizocarpon geographicum (L.) DC.

Abstract: Radial 14C/C profiles across three individuals of the crustose lichen Rhizocarpon geographicum (L.) DC. have been determined using accelerator mass spectrometry. These data were used to assess whether lifespan estimates can be determined in this species using 14C/C isotope ratio measurements. 14C/C profiles are relatively flat with Δ14C values (deviations from the modern radiocarbon standard) for the radial samples displaying a small spread ranging from 130 to 200 per mil. The data are consistent with carbon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 8 publications
0
25
2
Order By: Relevance
“…The results suggest there is not a statistically significant difference in the Table 3 Average radiocarbon (∆ 14 C) data from lichens analyzed in this study and reported by Bench et al (2001Bench et al ( , 2002 Table 5. The data provides no evidence of a significant difference between the δ 13 C values for the Caloplaca and Lecania species when comparing their isolated calcium oxalate pruina separated from the lichen tissues, the lichen tissues themselves, nor the δ 13 C tis − δ 13 C ox differences for the 2 species.…”
Section: ∆ 14 C Values Of Lichens Growing On Limestone and Sandstonementioning
confidence: 55%
See 3 more Smart Citations
“…The results suggest there is not a statistically significant difference in the Table 3 Average radiocarbon (∆ 14 C) data from lichens analyzed in this study and reported by Bench et al (2001Bench et al ( , 2002 Table 5. The data provides no evidence of a significant difference between the δ 13 C values for the Caloplaca and Lecania species when comparing their isolated calcium oxalate pruina separated from the lichen tissues, the lichen tissues themselves, nor the δ 13 C tis − δ 13 C ox differences for the 2 species.…”
Section: ∆ 14 C Values Of Lichens Growing On Limestone and Sandstonementioning
confidence: 55%
“…Moreover, the 14 C values from the limestone samples are consistently greater than values obtained by Bench et al (2001;2002) from analyses of Caloplaca trachyphylla (mean 14 C = 175.8 ± 70.5‰) growing on sandstone and Rhizocarpon geographicum (mean ∆ 14 C = 152.6 ± 19.8‰) growing on siliceous rocks (Table 3). Thus, the limestone specimens have more atmospheric carbon that must have been incorporated during an earlier period when the atmospheric 14 CO 2 concentration was higher (due to bomb 14 C production).…”
Section: ∆ 14 C Values Of Lichens Growing On Limestone and Sandstonementioning
confidence: 78%
See 2 more Smart Citations
“…The levels of the three carbohydrates were present at much higher concentration in the areolae than in the hypothallus which suggests that restriction of transport from areolae to hypothallus as hyphae age might be one explanation for the decreasing growth of larger R. geographicum thalli. Studies of C-14/C profiles across thalli of R. geographicum using mass spectroscopy, however, have provided little information to explain the growth curve (Bench et al 2001). The profile across thalli was flat and with little spread.…”
Section: Factors Determining the Growth Rate-size Curvementioning
confidence: 99%